THE APPLICATION OF LISTEN-READ-DISCUSS (L-R-D) STRATEGY TO IMPROVE READING SKILL AT THE FIRST GRADE OF SMPN 10 PAREPARE - Eralisa; Mujahidah (Inspiring: English Education Journal, 2019)
This study aim to find out the difference in reading skill between students who are taught of using L-R-D strategy and without using L-R-D strategy at the first grade of SMPN 10 Parepare. Furthermore, its aim is to determine the effectiveness of the Listen-Read-discuss strategy in reading skill learning at the first grade of Junior High School 10 Parepare. This research is an experiment design using pretest posttest design. The population of this research was all classes VII of SMP Negeri 10 Parepare, with samples of class VII 4 was experiment class and class VII 3 was control class. Data was obtained by Barret?s taxonomy reading skill test. The validity used is the validity of items that are assisted by computer item program. Reliability using the alpha Cronbach formula obtained result of 0.93. the data analysis technique used T-test with a significance of 5%. Before the data analysis was carried out using t-test technique, the prerequisite analysis test was carried out in the form of data distribution normality test and variant homogeneity test. The results of the pretest and posttest calculation of both groups are normal and homogeneous. T-test analysis of pretest data in reading skill of the experimental group and the control group, obtained -0.930 and (sig 0.357>0.05). This result indicates the initial skill of the experimental group and the control group were the same or there were no significant differences between the two group. T-test result of posttest in reading skill of the experimental group and the control group obtained -3.505 and (sig 0.000< 0.05) based on these data the results of this research showed significant differences between groups taught using of Listen-read-discuss strategy and without Listen-read-discuss strategy. The result of analysis T-test of the pretest and posttest showed that Listen-read-discuss strategy was effective to improve reading skill at the first grade of SMPN 10 Parepare.